2017
DOI: 10.1089/vbz.2017.2155
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the Occurrence and Human Infective Potential of Giardia duodenalis and Cryptosporidium spp. in Wastewater and Different Surface Water Sources of Western Romania

Abstract: From the group of parasitic protozoa, Giardia and Cryptosporidium are the most common pathogens spread in surface water sources, representing a continuous threat to public health and water authorities. The aim of this survey was to assess the occurrence and human infective potential of these pathogens in treated wastewaters and different surface water sources. A total of 76 western Romanian water bodies in four counties (Arad, Bihor, Caraș-Severin and Timiș) were investigated, including the effluents of wastew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…were recorded in different surface water types with a detection rate of 90.91% (10/11; 95% CI: 62.66–99.55) in wastewaters, 26.31% (5/19; 95% CI: 10.34–49.06) in brooks, 37.50% (3/8; 95% CI: 10.56–72.20) in irrigation channels, 31.25% (5/16; CI: 12.46–56.32) in lakes, and 36.36% (8/22; CI: 18.53–57.59) in ponds. The registered and successfully sequenced G. intestinalis assemblages were: assemblage E (n = 12) in all tested water bodies, assemblage AII (n = 9) in all tested water bodies except for ponds, and the domestic/wild canid specific assemblage D in a pond [97]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…were recorded in different surface water types with a detection rate of 90.91% (10/11; 95% CI: 62.66–99.55) in wastewaters, 26.31% (5/19; 95% CI: 10.34–49.06) in brooks, 37.50% (3/8; 95% CI: 10.56–72.20) in irrigation channels, 31.25% (5/16; CI: 12.46–56.32) in lakes, and 36.36% (8/22; CI: 18.53–57.59) in ponds. The registered and successfully sequenced G. intestinalis assemblages were: assemblage E (n = 12) in all tested water bodies, assemblage AII (n = 9) in all tested water bodies except for ponds, and the domestic/wild canid specific assemblage D in a pond [97]. …”
Section: Resultsmentioning
confidence: 99%
“…in the environment highlighted that to date, relatively little is known about the occurrence and genetic diversity of these parasites in natural water supplies. Reports were available from the Czech Republic, Hungary, Poland and Romania [24,55-58,72,73,80-84,96-97]. …”
Section: Discussionmentioning
confidence: 99%
“…Australia (King et al 2015a;Zahedi et al 2018), Brazil andPeru (Ulloa-Stanojlović et al 2016;Martins et al 2019), China (Feng et al 2009;Li et al 2012;Huang et al 2017), Japan (Hashimoto et al 2006;Hirata and Hashimoto 2006), Switzerland and Germany (Ward et al 2002), the USA (Xiao et al 2001;Zhou et al 2003) and Tunisia (Ben Ayed et al 2012) (Table 2). While in Europe, a number of studies have reported that C. parvum is the dominant species in wastewater (Hänninen et al 2005;Spanakos et al 2015;Imre et al 2017;Ramo et al 2017). In other countries such as China, Iran, Tunisia and the USA, livestock-associated species such as C. andersoni and C. xiaoi dominate in wastewater samples (Xiao et al 2001;Liu et al 2011;Ben Ayed et al 2012;Hatam-Nahavandi et al 2016;Ma et al 2019) (Table 2).…”
Section: Occurrence Of Protozoans In Wastewatermentioning
confidence: 97%
“…As a result, even at low concentrations, these parasites are worrisome, due to the high observed risk of infection, as shown by Sato et al in 2013 [37]. Several studies indicated that lake/pond water was found to harbor Cryptosporidium and Giardia (oo)cysts [38][39][40]. This is contrary to our presented results where we found that the frequency and counts of both Giardia and Cryptosporidium (oo)cysts were zero in the investigated samples of lakes/ponds and soils.…”
Section: Resultsmentioning
confidence: 99%